Kajian Sosiologi Sastra dalam Novel Tingka Karya Nicco Machi - Julita Larashati; Ela Fatmawati Azid; Hetilaniar Hetilaniar; Darwin Effendi (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2026)
This study aims to analyze Nicco Machi's novel "Rata" through a sociological approach to literature, incorporating Lucien Goldmann's genetic structuralism theory. The background of this research is based on the view that literary works reflect the social structures and class ideologies that gave rise to them. The novel "Rata" depicts the realities of urban life, with its diverse social strata, economic conflicts, and existential problems faced by its characters. This study employed a qualitative descriptive method with content analysis techniques. Data were collected through in-depth reading of the text, identifying units of social meaning, and interpreting the narrative structure, which reflects the relationship between individuals and society. The results indicate that the novel portrays social inequality, individual alienation due to economic pressures, and identity struggles in the modern urban space. The narrative structure and characters in the novel "Rata" reflect the collective consciousness of the middle class, caught between idealism and materialistic reality. Thus, this work can be read as a social representation of changing values ​​and power relations in contemporary Indonesian urban society.